2007
DOI: 10.1530/rep-06-0168
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell degranulation in rat uterine cervix during pregnancy correlates with expression of vascular endothelial growth factor mRNA and angiogenesis

Abstract: Vascular growth of the uterine cervix during pregnancy is associated with mast cell (MC) degranulation. To better understand the mechanism underlying this process, uterine cervices of intact pregnant rats were dissected and endothelial cell proliferation was measured by a bromodeoxyuridine incorporation technique. Total vascular endothelial growth factor (VEGF) mRNA expression and the relative abundance of VEGF splice variants (120, 164, and 188) were determined by RT-PCR. VEGF protein expression was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 54 publications
0
23
0
1
Order By: Relevance
“…Until recently, their contribution to pregnancy establishment and/or maintenance was unclear as contradictory reports could be found in the literature. In pregnant rats, MC degranulation was shown to have positive effects on cervical angiogenesis (66). In mice, Menzies et al found no role for these cells in labor in a syngeneic context when employing C57BL/6J- Kit W-sh/W-sh mice (67).…”
Section: Uterine Mast Cellsmentioning
confidence: 99%
“…Until recently, their contribution to pregnancy establishment and/or maintenance was unclear as contradictory reports could be found in the literature. In pregnant rats, MC degranulation was shown to have positive effects on cervical angiogenesis (66). In mice, Menzies et al found no role for these cells in labor in a syngeneic context when employing C57BL/6J- Kit W-sh/W-sh mice (67).…”
Section: Uterine Mast Cellsmentioning
confidence: 99%
“…The serum samples stored at −20°C were thawed, and the serum levels of E2 and P were determined by RIA after ethyl ether and hexane (Merck, Buenos Aires, Argentina) extraction, respectively (Bosquiazzo et al, 2007). The antibodies were provided by G. D. Niswender, and the labeled hormones were purchased from PerkinElmer Life and Analytical Sciences (Boston, MA, USA).…”
Section: Hormone Assaysmentioning
confidence: 99%
“…Sapmaz et al (2015) reported that cromolyn treatment induced a significant reduction in VEGF-a in the lung parenchyma of the male Fischer 344 rats with aspiration-induced fibrosis (Chang et al 2014). Bosquiazzo et al (2007) used disodium cromoglycate to inhibit mast cells degranulation and, related to this, to study angiogenesis variability in rat uterine cervix during pregnancy. They reported an inhibition of VEGF mRNA by disodium cromolyn and also a decreased endothelial cell proliferation.…”
Section: Discussionmentioning
confidence: 99%